Estimating SIT-driven population reduction in the Mediterranean fruit fly, Ceratitis capitata, from sterile mating. Issue 2 (April 2014) - Juan-Blasco, M.; Sabater-Muñoz, B.; Pla, I.; Argilés, R.; Castañera, P.; Jacas, J. A.; Ibáñez-Gual, M. V.; Urbaneja, A.
Abstract Area-wide sterile insect technique (SIT) programs assume that offspring reduction of the target population correlates with the mating success of the sterile males released. However, there is a lack of monitoring tools to prove the success of these programs in real-time. Field-cage tests were conducted under the environmental conditions of the Mediterranean coast of Spain to estimate: (a) the mating success of sterile Vienna-8 (V8) Ceratitis capitata males using molecular markers and (b) their efficacy to reduce C. capitata populations under six release ratios of wild females to wild males to V8 males (1:0:0, 1:1:0, 1:1:1, 1:1:5, 1:1:10, and 1:1:20). Statistical models were developed to predict: (a) the number of females captured in traps, (b) sperm ID (sterile or not) in spermathecae of the trapped females, and (c) the viable offspring produced, using release ratio and temperature as predictors. The number of females captured was affected by relative humidity. However, its influence in the model was low. Female captures were significantly higher in ratios 1:0:0 compared to ratios where V8 males were released. The proportion of V8 sperm in spermathecae increased with temperature and with the number of V8 males released, but leveled off between ratios 1:1:10 and 1:1:20. In all seasons, except winter (no offspring), viable offspring increased with temperature and was lowest for ratio 1:1:20. For the first time, a strong negative relationship between proportion of V8 sperm detected by molecular tools and C. capitata offspring was established. The models obtained should contribute to enhance the efficacy of SIT programs against this pest.